Hydrogen from Dark Fermentation of the Organic Fraction of Waste Diapers: Optimization Based on Response Surface Experiments - Sotelo-Navarro, Perla X.; Poggi-Varaldo, Héctor M. (Frontiers in Energy Research, 2021)
Waste diapers (WD) handling and disposal in Mexico are typically based on their burial in dumping sites and landfills. Practically reclaiming and recycling of WD are non-existent. The clean diapers are composed of cellulose fibres (37–43% db), hemicellulose (5–9%), lignin (4–7%), protein (<1), plastics (polypropylene and polyethylene) (12–16%), absorbent sodium polyacrylate (14–18%), and elastic and adhesives tapes (9–12%). The latter can be valuable resources. WD composition is similar to clean diaper, although humidity is very high, and the ranges of faeces and urine are 1.5–2.5 and 6–9% dry weight, respectively. International literature searches indicate that there is some research on composting, fungal biodegradation, and methanogenic co-digestion of waste activated sludge with the organic fraction of waste diapers (OFWD.) However, research on dark fermentation of OFWD is limited. In this work, the generation of biohydrogen from dark fermentation of OFWD was optimised. We used the response surface methodology (RSM). Independent variables were the temperature of operation (37–55°C), ratio C/N of the feed (30, 40 gC/gN), and initial total solids of the feed (TSi) (15, 25%). The dependent (response) variables examined were Y’H2 (H2 produced per initial g of dry matter), contents of low molecular weight organic solvents and acids, lactic acid, the ratio A/B (acetic-to-butyric acid), and the quotient organic acids C2 to C4-to-solvents. The predicted maximum Y’H2 occurred at the combination of factors of 43 gC/gN, 12% and 31°C; its value was 2.79 mmolH2/gTS; its experimental validation gave 2.48 mmolH2/gTS, which shows a good agreement between values (11% lower than the predicted value). The maximum of Y’H2 with OFWD compared very favourably with bioH2 values obtained from a wide variety of wastes (organic municipal residues, agricultural wastes, etc.) using the same batch type fermentation with intermittent venting. Interestingly, the predicted temperature optimum fell in the lower side of the mesophilic range. Process heating savings would be in the order of 60.0 and 27.2% for thermophilic and mesophilic operation, respectively. In this way, it would be a contribution to the sustainability of the dark fermentation of OFWD. This result was somewhat counterintuitive and strongly indicates the usefulness of the response surface methodolog for analyzing the experimental results and uncovering favourable, although unexpected conditions.